The Influence of Utilizing Village Funds on Increasing Development, Empowerment and Its Implications for Community Welfare (Study on Village Communities in Posigadan District, South Bolaang Mongondow Regency) - Sahabi, Ansar; Mohamad, Roni; Syawaluddin, Syawaluddin; Ajuna, Luqmanul Hakiem (MediaTrend, 2023)
This study aims to determine the effect of village fund utilization on increased development, empowerment and its implications for welfare ( Studies on Village Communities in Posigadan District and South Bolaang Mongondow Regency). The population in this study is the people of Posigadan District, while the sample is 150 respondents. Data collection techniques employed observation, questionnaires, and documentation. The data analysis method in this study used Structural Equation Modeling (SEM) technique with using SPSS AMOS Version 23.0 application. The results of the study show that (1) utilization of village funds has a positive and significant effect on the development, (2) utilization of village funds has a positive and significant effect on the empowerment, (3) utilization of village funds has a positive and significant effect on the welfare, (4) village development has a positive and significant effect to welfare, (5) community empowerment has a positive and significant effect on welfare as well. As for the indirect effect, it indicates that the utilization of village funds has a positive and significant effect on welfare through development, and community empowerment as an intervening variable in Posigadan District.